PARTISIPASI POLITIK PEREMPUAN DALAM PEMILU KADA 2024 DI PROVINSI LAMPUNG: Women's Political Participation in the 2024 Elections (Regional Head Elections) in Lampung Province - SUCI LESTARI; Fitriani Ali Zein, Kiki (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2024)
This study aims to analyze women's political participation and representation in the 2024 elections in Lampung Province. A qualitative descriptive methodology was used, focusing on literature from official sources, such as government agencies, NGOs, and research institutions. The theory of women's political participation highlights the importance of active involvement in politics to achieve gender equality and ensure that women's interests are represented in public policy. Conversely, representative theory by Hanna Pitkin emphasizes the need for alignment between societal demographics and political representation. The findings indicate that women's representation in Lampung is stagnating, significantly below the national quota target, reflecting a stagnant participation trend that may decline if existing challenges are not addressed. Women's involvement in politics is also hindered by male dominance within party structures. Inhibiting factors include socio-cultural norms, limited access to education and political information, and a lack of opportunities and resources. This research aims to enhance understanding of women's rights and roles in local politics and encourage their political engagement. Keywords Women's Political Participation, Women's Representation, Elections, Lampung